Changes in Demand and Expenses for Food in Households in Poland - Anna Kowalska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The aim of the work is to assess the demand for food among households in Poland and the changes that occurred in this demand in the years 2000-2016. In addition, changes in the consumption of selected food products over a period of 10 years depending on the socio-economic group of the household have been evaluated. The research material consists of secondary data obtained from the publication of the Central Statistical Office in the years 2000-2016. The study uses descriptive statistics methods. The income situation of households in Poland during the period under review significantly improved. In the analysed years, monthly expenses on food products per one person grew slower than total expenditure and disposable income. The analysis of the research material showed a decrease in consumption of the majority of discussed food products. The increase in demand occurred in the case of yoghurts as well as cheese and curd. The analysis divided into socio-economic groups of the households showed significant variation in the consumption of sugar, fish and seafood as well as oils and fats.